Literature Review Platform Digital Sebagai Media dalam Mengembangkan Usaha Mikro Kecil Menengah - Mario Pradana Putra (Syntax Literate, 2022)
There are now more opportunities available than ever before as the digital revolution continues to permeate every sector of the economy. The resource-based perspective hypothesis asserts that digital transformation improves both innovative capabilities and the overall performance of businesses. Due to the proliferation of small and medium-sized firms (SMEs) and the relatively significant role they play in the economy of the local community, the current digital age is fraught with a number of challenges that have arisen as a result. The key challenges that small and medium-sized enterprises (SMEs) have when attempting to digitalize their operations include a lack of cash resources, low knowledge resources, and limited grasp of technology concepts. Digital platform built on an ecosystem that assists small and medium-sized organizations in better adapting to settings that are unpredictable and changing by combining key information sources and personalizing internal and external resources.